The Comparison of Utilizing Piezotome and Surgical Disc in Ridge Splitting of Atrophic Edentulous Maxillary Ridge - Shahakbari, Reza (J Maxillofac Oral Surg, 2019)
OBJECTIVE: Narrow dentoalveolar ridges remain a serious challenge for the successful placement of dental implants. The aim of this study was to compare the clinical outcomes of piezosurgery versus surgical disc on ridge splitting in the atrophic edentulous maxilla. MATERIALS AND METHODS: This was a double-blinded randomized clinical trial. The healthy subjects who were candidates for maxillary ridge expansion were included in this experiment. Patients were randomly divided into two groups: piezosurgery group and surgical disc group. The width of the bone in the surgical site was measured by surgical calliper before the osteotomy. The bone width was remeasured after ridge-split completion (before suturing) and during the implant placement (4 months later). Then data were analysed by SPSS software, and the P value was set at 0.05. RESULTS: The study sample size included 20 cases. Our outcomes showed that both techniques (surgical disc and piezotome) were effective in ridge splitting (P < 0.001). However, the average bone width which was obtained after ridge splitting was significantly higher in the piezosurgery group (P < 0.05). CONCLUSION: It can be concluded that both methods of piezosurgery and surgical disc can significantly lead to increase in the ridge width. However, the piezosurgery technique was more effective in ridge splitting.